Social Entrepreneurship and Gender Empowerment: A Systematic Literature Review on Innovation, Inclusion, and Sustainable Development (2020–2025) - Silvia Annisa (Talenta Publisher, 2026)
Social entrepreneurship has emerged as a transformative approach that integrates innovation, inclusion, and sustainability to advance gender empowerment. This study provides a systematic literature review (SLR) of research published between 2020 and 2025, examining how social enterprises contribute to women’s empowerment through inclusive and sustainable business models. Following the PRISMA 2020 protocol, a comprehensive search was conducted using the Scopus database, limited to peer-reviewed, open-access articles in English within the social sciences and business fields. From 180 identified records, 20 duplicates were removed, resulting in 160 studies included in the final synthesis. Thematic analysis revealed five interconnected themes: (1) innovation and inclusive business models; (2) gender empowerment and leadership; (3) community development and social value creation; (4) barriers and enablers of women’s entrepreneurship; and (5) sustainability and institutional support. The findings demonstrate that empowerment through social entrepreneurship is multidimensional, encompassing individual agency, social capital, and institutional transformation. Innovation and open collaboration serve as catalysts for inclusion, while policy and institutional frameworks determine long-term sustainability. The study integrates social capital theory, inclusive innovation, and feminist institutionalism to explain how empowerment emerges within entrepreneurial ecosystems. It concludes that gender empowerment in social entrepreneurship is both a process and an outcome of systemic change—requiring inclusive policies, capacity building, and equitable access to innovation. This review contributes to theory and practice by providing a comprehensive framework linking social entrepreneurship to gender-responsive sustainable development.